2016
DOI: 10.1155/2016/1353497
|View full text |Cite
|
Sign up to set email alerts
|

Agroindustrial Wastes as Alternative for Lipase Production by Candida viswanathii under Solid-State Cultivation: Purification, Biochemical Properties, and Its Potential for Poultry Fat Hydrolysis

Abstract: The aims of this work were to establish improved conditions for lipase production by Candida viswanathii using agroindustrial wastes in solid-state cultivation and to purify and evaluate the application of this enzyme for poultry fat hydrolysis. Mixed wheat bran plus spent barley grain (1 : 1, w/w) supplemented with 25.0% (w/w) olive oil increased the lipase production to 322.4%, compared to the initial conditions. When olive oil was replaced by poultry fat, the highest lipase production found at 40% (w/w) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…However, microbial lipases form the most widely used class of enzymes due to their selectivity, lower production cost, ease of genetic manipulation, high productivity, regiospecificity, stereospecificity, broad substrate specificity and ability to catalyze heterogeneous reactions at the interface of water soluble and water insoluble systems [8,[11][12][13]. Microorganisms such as bacteria, yeast, fungi and actinomycetes have been reported as potential producers of lipase [14][15][16][17]. They are found in different habitats, including industrial wastes, vegetable oil processing industries, dairy industries and oil-contaminated sites, among others [18].…”
Section: Introductionmentioning
confidence: 99%
“…However, microbial lipases form the most widely used class of enzymes due to their selectivity, lower production cost, ease of genetic manipulation, high productivity, regiospecificity, stereospecificity, broad substrate specificity and ability to catalyze heterogeneous reactions at the interface of water soluble and water insoluble systems [8,[11][12][13]. Microorganisms such as bacteria, yeast, fungi and actinomycetes have been reported as potential producers of lipase [14][15][16][17]. They are found in different habitats, including industrial wastes, vegetable oil processing industries, dairy industries and oil-contaminated sites, among others [18].…”
Section: Introductionmentioning
confidence: 99%
“…The choice of substrate will depend on the nutritional needs of the microbial species to produce the target compound [93]. Among the substrates used for the production of lipase, stand out cottonseed cake [80], soybean bran, sugarcane bagasse [94], wheat bran, spent barley [95], olive mill waste [81], by-products from corn oil refining [96] and others reported in the literature efficiently used individually or supplemented with other nutritional components. In addition to solving an environmental problem, through the alternative use instead of improper disposal, the use of agroindustrial wastes and byproducts allows the reduction of the costs of the biotechnological process since they are abundant and have a low cost [93,97,98].…”
Section: Solid-state Fermentation Substrates and Bioreactorsmentioning
confidence: 99%
“…Crops with ground soybean tegument were supplemented with the addition of different nitrogen sources at a concentration of 5% (m/m) [19]: casein, ammonium chloride, yeast extract, and urea.…”
Section: Supplementation With Nitrogen Sourcesmentioning
confidence: 99%
“…The substrates were supplemented with 10 mL of Vogel salts solution without nitrogen source and 40% of olive oil or poultry fat. Almeida et al (2016) [19] observed that supplementing wheat bran with 5% (w/w) yeast extract resulted in a 3.8-fold increase in lipase production when compared to cultivation without the addition of the source. of nitrogen.…”
Section: Supplementation With Nitrogen Sourcesmentioning
confidence: 99%